Sorption properties of magnesium-potassium phosphate matrix - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Saenko, S.Y.; Shkuropatenko, V.A.; Tarasov, R.V.; Fedorets, I.D. (Вопросы атомной науки и техники, 2015)
Sorption characteristics of fine-dispersed magnesium-potassium phosphate ceramics KMgPO₄·6H₂O for immobilization of ¹³⁷Cs was investigated. The Cs specific capacity 2.97 mg/g at pH=4 was detected. The high selectivity of the ion exchange of KMgPO₄·6H₂O out of dilute solutions was caused by various values of hydration radii of potassium and cesium. There is change in solution pH in dynamics studies toward higher values, apparently due to leaching of movable potassium out of ceramics. The high chemical and radiation resistance of ceramic are confirmed. Досліджені сорбційні характеристики дрібнодисперсної магній-калій-фосфатної кераміки KMgPO₄·6H₂O для іммобілізації ¹³⁷Cs. Виявлено високу ємність по цезію, що складає 2.97 мг/г при рН=4. Висока вибірковість іонного обміну з розведених розчинів, обумовлена різною величиною гідратаційних радіусів калію і цезію в матриці KMgPO₄·6H₂O. Спостерігається зміна рН розчинів у динаміці досліджень у бік більш високих значень, очевидно, за рахунок вилугування рухливого калію з кераміки. Підтверджено високу хімічну і радіаційну стійкість даної кераміки. Исследованы сорбционные характеристики мелкодисперсной магний-калий-фосфатной керамики KMgPO₄·6H₂O для иммобилизации ¹³⁷Cs. Обнаружена высокая емкость по цезию, которая составляет 2.97 мг/г при рН=4. Высокая избирательность ионного обмена из разбавленных растворов обусловлена различной величиной гидратационных радиусов калия и цезия в матрице KMgPO₄·6H₂O. Зарегистрировано изменение pH растворов в динамике исследований в сторону более высоких значений, по-видимому, за счет выщелачивания подвижного калия из керамики. Подтверждены высокие химическая и радиационная устойчивости данной керамики.